METRONIDAZOLE INDUCES SIGNIFICANT PATHOLOGICAL ALTERATIONS IN THE MALE REPRODUCTIVE SYSTEM OF MICE - Al – Timimi, Z. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study was aimed to investigate the possible effects caused by the antibiotic, metronidazole, on the histology of the testis and the morphology of the sperms of mice. To achieve this, adult male albino Swiss Mice were orally administrated with 0.1 ml (100 mg kg ) of the commercially used metronidazole (Flagyl) for 60 consecutive days. The results showed significant decreases (p<0.05) in the mean weight of body and testis in the treated mice as compared to the distilled water-treated control group. The treatment also caused several histopathological changes in the testis which included necrosis, congestion, hemorrhage, edema, germ cell downfall and rupture in the seminiferous tubules. The tests of the sperm morphology revealed a number of deformations as a result of the treatment, such as the appearance of headless, bend, broken-tailed, hook-tailed, and two-headed sperms, as well as sperms with cytoplasmic droplets. We conclude that from these results that orally administered Metronidazole exerts negative effects on the male reproductive system of mice .